Analisis Diakronik pada Kata “Geisha” dalam Perspektif Masyarakat Luas (NAWA: Journal of Japanese Studies, 2025)
This study examines the diachronic semantic evolution of the term geisha from the Edo era to the Reiwa period, highlighting how its meaning has shifted in response to changing social, cultural, political, and global influences. Using Stephen Ullmann’s theory of semantic change specialization, generalization, amelioration, and pejoration alongside Stuart Hall’s theory of cultural representation, the data collection method is carried out through a literature review that involves the application of Geisha language from several historical periods (Edo, Nishijima, Zaisho, Shoka, Reiwa). In addition, we gathered information in the form of content analysis from mainstream media as well as academic writing to understand current perspectives. We also requested data regarding searches of the Japanese corpus and commonly used translations to identify shifts in meaning for further analysis. Data analysis is conducted using the theory of change proposed by Stephen Ullmann (1962) in the context of semantics. The types of meaning changes include pejoration, elevation, generalization, and specialization. This research reveals that geisha initially referred to male entertainers before becoming specialized as a term for female artists highly skilled in traditional Japanese arts such as music, dance, and conversation. This study concludes that the meaning of geisha has never been fixed but has continually evolved through complex discursive processes. It demonstrates that diachronic semantic analysis is not only essential in understanding linguistic development but also crucial in unpacking shifting cultural identities and global misrepresentations over time.